Colorectal Cancer Test Use Among Hispanic and Non-Hispanic U.S. Populations - Lori A. Pollack, MD, MPH; Donald K. Blackman, PhD; Katherine M. Wilson, PhD, MPH; Laura C. Seeff, MD; Marion R. Nadel, PhD (Centers for Disease Control and Prevention, 2006)
Introduction Although colorectal cancer mortality rates in the general U.S. population declined slightly from 1992 to 2000, the rates for Hispanic men and women did not. Disparity in colorectal cancer screening among Hispanics may be an important factor in the unchanged mortality trends. This study examined rates of colorectal cancer test use among Hispanic and non-Hispanic adults in the United States. Methods Using sampling weights and logistic regression, we analyzed colorectal cancer test use among 5680 Hispanic and 104,733 non-Hispanic adults aged 50 years and older who participated in the 2002 Behavioral Risk Factor Surveillance System. We estimated the percentages and adjusted odds ratios (ORs) of the respondents' reported test use by sociodemographic characteristics, health care access, and state or territory of residence. Results Hispanic respondents aged 50 and older reported having had either a fecal occult blood test within the past year or a lower endoscopy (sigmoidoscopy or colonoscopy) within 10 years less frequently (41.9%) than non-Hispanic respondents (55.2%). Rates of test use were lower for respondents who reported less education, lower income, no health insurance, and no usual source of health care, regardless of Hispanic ethnicity. After adjusting for differences in education, income, insurance, and having a usual source of health care, Hispanic respondents remained less likely than non-Hispanic respondents to report colorectal cancer testing (OR for fecal occult blood test, 0.66; 95% confidence interval [CI], 0.56-0.81; OR for lower endoscopy, 0.87; 95% CI, 0.77-0.99). Greater disparity in screening rates between Hispanics and non-Hispanics was observed in Colorado, California, and Texas than in other states. Conclusion A disparity exists between Hispanic and non-Hispanic U.S. adults in colorectal cancer test use. This disparity varies among the states, highlighting the diverse health care experience of Hispanic adults in the United States.